Model‐Based Process Development in the Biopharmaceutical Industry - Sejergaard, Lars; Ahmadian, Haleh; Hansen, Thomas B.; Staby, Arne; Hansen, Ernst B. (Preparative Chromatography for Separation of Proteins, 2017)
This chapter presents an example of how mechanistic modeling may be applied in the biopharmaceutical industry. It shows how the different quality by design (QbD) elements of risk assessment and process knowledge are linked through identification of key critical quality attributes (CQAs), which may be affected by the step and the different process parameters responsible for such influence on the CQAs. The chapter contains examples of MATLAB programming code, which can be directly implemented for modeling of size exclusion chromatography (SEC). FVIII is one of the most complex recombinant proteins that has been produced, and as such it may be regarded as a highly complicated molecule to be subject to process modeling. Given the fragile nature of FVIII molecules, a considerate purification process is needed after serum‐free (SF) cultivation. The turoctocog alfa process case study demonstrates that by only a few calibration experiments, a useful model can be established.